Identity, Community, and Technology: Reflections on the Facebook Group Inuit Hunting Stories of the Day - Castleton, Alexander (Études Inuit Studies, 2016)
In this article I reflect on a particular Inuit use of the social networking site Facebook: the group called Inuit Hunting Stories of the Day. I focus on two main issues. First, I discuss the logic behind current technologies as conceptualized by Albert Borgmann (e.g., 1984), who states that rather than being neutral tools, modern devices foster a particular “taking-up” with the world that leads to disengagement from community and meaningful practices. Arguing against this view, I discuss how Inuit Hunting Stories of the Day is an example of how the internet and Facebook are appropriated and provide meaningful engagement. Second, I follow anthropologist Claudio Aporta’s (2013) notion of ecology of technology and argue that the relationship between technology and Inuit has to be understood within an ecological framework that encompasses the broader context of political, economic, and social change, which are intertwined with the use, appropriation, adoption, and adaptation of technology. Drawing from the ecology of technology perspective, it is my central argument that technology and computer-mediated communication bring proximity to cultural practices, activities, and the land rather than provoking distance and alienation from reality, as commonly expressed in dystopian notions.